Survival of an emerging foodborne pathogen : Group B Streptococcus (GBS) serotype III sequence type (ST) 283—under simulated partial cooking and gastric fluid conditions - Zwe, Ye Htut (2020)
Group B Streptococcus (GBS) was previously not known to be transmitted through food, but an outbreak investigation in Singapore in 2015 documented for the first time an association between GBS Type III Sequence Type 283 infection and consumption of raw fish dishes. As very little is known about the survival of GBS during heat treatment and the stomach transit, its survival under simulated conditions was studied, in comparison with that of Escherichia coli O157:H7 and Listeria monocytogenes. The mean D-values of four GBS strains ranging from 0.72 to 0.88 min in neutral pH tryptone soy broth at 56.4 °C and 0.44–1.43 min at pH 2.35 at 37 °C in simulated gastric fluid, were significantly lower (p < 0.05) than those of E. coli O157:H7 and L. monocytogenes. This study suggests possible factors other than acid or heat resistance of GBS to be instrumental to its pathogenicity.